2018
DOI: 10.3390/jcm7050090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oral Mucositis Occurrence in Oncologic Patients under Antineoplastic Therapy Submitted to the Low-Level Laser Coadjuvant Therapy

Abstract: Low-level laser therapy has been widely used in treating many conditions, including oral mucositis. The purpose of this study was to evaluate the occurrence of oral mucositis in patients undergoing antineoplastic therapy submitted to preventive and therapeutic treatment with low-level laser therapy. This cross-sectional study was carried out with 51 children and adolescents of both sexes with malignant neoplasias who developed oral mucositis and underwent low-level laser therapy. Data were collected on sex, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
2
8
0
4
Order By: Relevance
“…The incidence rate of OM in pediatric patients in our study was 73.5% for all grades and 23.5% for severe OM, which is in line with the results found in studies with the same population 2‐5 . The therapeutic approaches to avoid OM development are not available, but the prophylactic use of PDC 25‐27 and PBM 1,15,28‐31 has been reported to reduce the incidence and severity of this toxicity in cancer patients. Both incidence and severity of OM were shown to decrease after the application of PBM and PDC, 1 which was also confirmed in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The incidence rate of OM in pediatric patients in our study was 73.5% for all grades and 23.5% for severe OM, which is in line with the results found in studies with the same population 2‐5 . The therapeutic approaches to avoid OM development are not available, but the prophylactic use of PDC 25‐27 and PBM 1,15,28‐31 has been reported to reduce the incidence and severity of this toxicity in cancer patients. Both incidence and severity of OM were shown to decrease after the application of PBM and PDC, 1 which was also confirmed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Meeting this reasoning, the use of active agents, such as chlorhexidine, has been indicated in oral care and prevention of OM 27,32 . The effectiveness of intraoral PBM in the treatment of OM has been reported in some studies with hematological and solid cancer paediatric patients undergoing chemotherapy and/or HSCT, in reducing either the severity or the duration of this adverse effect 28‐31 . Using an intraoral PBM, the incidence of OM in our sample was 73.5%, which is similar to the value (77%) was reported by Treister et al 5 using an extraoral approach, but lower than the value reported by Eduardo et al, 10 who observed mild mucositis (WHO grades I and II) in all of their 51 cases.…”
Section: Discussionsupporting
confidence: 84%
“…The jugal / palate mucosa and the labial mucosa were the sites most commonly compromised. A cross-sectional study with children and adolescents undergoing CT observed that the tongue and jugal mucosa areas were most frequently compromised by SOM ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is not yet a universal protocol for the clinical management of this condition, the current available therapies involve mainly local and systemic anti-inflammatory and analgesic drugs, oral hygiene protocols, and photobiomodulation (PBM) [7]. PBM shows efficacy in the clinical management of OM, either in cases caused by chemotherapy [8,9] or radiotherapy [10,11], or in cases where OM was caused by the use of combination of these two treatment modalities [12]. PBM is currently considered the standard treatment for OM lesions, especially because it does not cause the systemic toxicity that pharmacological treatment can generate [1,13,14].…”
Section: Introductionmentioning
confidence: 99%